A Case Study of Cohesion in Academic Texts trough Systemic Functional Linguistics - Dwi Putri Lestari; Nurlela Nurlela (JALL (Journal of Applied Linguistics and Literacy), 2026)
This study aims to analyze the use of cohesive devices in undergraduate thesis abstracts by English Department students in Indonesia through the Systemic Functional Linguistics (SFL) approach. The data consist of 20 thesis abstracts selected from three public and private universities and were analyzed qualitatively focusing on grammatical cohesion (reference, substitution, ellipsis, conjunction) and lexical cohesion (repetition, synonym, antonym, collocation). The findings reveal that reference and conjunction are the most dominant grammatical cohesive devices; however, errors such as ambiguous references and illogical conjunction usage are frequently found. On the lexical level, repetition serves as the main strategy, while the use of synonyms and collocations remains limited, reducing lexical variety and the clarity of arguments. These findings underscore the importance of integrating SFL into academic writing instruction to improve students’ cohesion competence.